Argumentasi Tauhidik Dalam Perilaku Sosial-Agama - Hadining, Hasanain Haikal (FIKRAH, 2017)
Humans need religion as a hand of living. Islam is a religion of the majority that adopted of the society in Indonesia. Islam increasingly faces heavy challenges, an example are materialism and the doctrine of terrorism which many interesting sympathy from lay of people. Threfore the knowledge of the true of tawhid understanding needs to be communicated to the public, in order that the society can be strong to grip of life. Th people with knowledge of true tawheed can reach safety in the world of life and in the hereaftr. Tawheed is the subject of faith, God should not be like a creature (mujassimah or musyabbihah), and the existence of God is without place and without direction. Th research method in this article is descriptive qualitative usting library research approach supported by historical and sociological studies.